FEASIBILITY STUDY OF A RAILWAY CONSTRUCTION PROJECT AS INTERMODAL TRANSPORTATION IN TANJUNG PERAK PORT - Kevin Arga; Budi Susetyo; Syafwandi Syafwandi (Universitas Mercu Buana, 2021)
The growth of container flows that is not supported by infrastructure needs has caused goods congestion at Tanjung Perak Port. The situation has an impact on the flow of goods and makes container mobilization stop flowing. Railway infrastructure construction is expected to overcome the problem of goods congestion, especially because this project will be integrated with other transportation at the Port in an intermodal transportation system. The Delphi method is used as an approach to get the dominant aspect to be analyzed in a feasibility study of a railway construction project at the Port of Tanjung Perak. Delphi method results show that the financial aspect and market aspect are the dominant parameters to be analyzed in the feasibility study of a railway construction project. The results of the market feasibility analysis showed that 87.67% of stakeholders agreed with the railway development project plan, with a target market of 19.99% of the number of containers and absorption of around 84% of the target market. The results of the financial feasibility analysis are obtained, the Net Present Value (NPV) is 1,184,370> 0 (profitable project), the Benefit-Cost Ratio (BCR) is 1.39 ≥ 1 (the project is feasible), and the value of the Internal Rate of Return (IRR) is 13%> MARR, (investment is feasible). From the results of the financial feasibility analysis, the railway construction project is categorized as possible. Meanwhile, the break-even point for this project is in the 12th year with the results of a profit-loss analysis showing that in the fourth year, the railway operational activities have shown a positive trend/profit.